2006
DOI: 10.1159/000091052
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Artificial Caries on the Occlusal Surfaces with Polarization-Sensitive Optical Coherence Tomography

Abstract: Polarization-sensitive optical coherence tomography (PS-OCT) is a nondestructive imaging system that can utilize near-infrared (IR) light to produce depth-resolved images of dental enamel and has the potential to monitor early enamel occlusal caries. The objective of this study was to investigate the relationship between the magnitude of backscattered light and depolarization recorded by PS-OCT with changes in the enamel mineral volume in an artificial caries model. Artificial lesions were created on a selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
142
2
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(155 citation statements)
references
References 68 publications
3
142
2
8
Order By: Relevance
“…Monitoring in vivo carious lesion changes could be helpful with this device. [34][35][36] A combination of near infrared radiation (NIR) imaging with PS-OCT was also described to acquire depthresolved images. Combining this technology with a short-pulsed CO 2 laser ablation system would allow for the selective removal of dental caries.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring in vivo carious lesion changes could be helpful with this device. [34][35][36] A combination of near infrared radiation (NIR) imaging with PS-OCT was also described to acquire depthresolved images. Combining this technology with a short-pulsed CO 2 laser ablation system would allow for the selective removal of dental caries.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…37 Whatever numerical values given by the device, 35,36 visual inspection remains an essential component in making the final decision: to drill or not to drill. Indeed it is more the complexity of the shape, depth and the width of the grooves which governs clinical decision, meaning that before the diagnostic step the pits need to be perfectly clean.…”
Section: Illustrations With Clinical Casesmentioning
confidence: 99%
“…Based on this finding, it has been suggested that the reflectivity from the lesion area can be directly determined and then used as a measure of the lesion severity 19,20) . It has also been shown that shallow lesions exhibit a loss of penetration depth in OCT images and this is correlated with the mineral loss that can be detected with microradiography 21) .…”
Section: Discussionmentioning
confidence: 99%
“…65 After that, a series of studies using an artificial caries model and PS-OCT was performed to evaluate caries under composite sealants and restorations, the severity of interproximal caries lesions, occlusal surface caries, remineralization of the lesion, inhibition of demineralization by anticaries tools such as fluoride or lasers, demineralization of enamel by CO2 lasers, demineralization of exposed root surfaces, and de-/re-mineralization of dentin. 7,[66][67][68][69][70][71][72][73][74][75] In addition, this group compared the near-infrared (NIR) transillumination to PS-OCT and combined these methods with other optical techniques into image-guided laser ablation systems. [76][77][78] Recently, the study of automated analysis algorithms to assess enamel demineralization and the use of novel cross-polarization OCT were reported.…”
Section: Applications In Caries Detectionmentioning
confidence: 99%
“…6 The effectiveness of this nonsurgical therapy is contingent on detecting the lesion in the outer enamel and requires imaging modalities that can safely and accurately monitor the success of such treatment. 7 Visual examination and probing with a sharp explorer is a rather subjective method depending on the examiner' s experience and training. 8 Early caries detection using optical coherence tomography: a review of the literature Clinical radiology is another widely used method that has poor sensitivity for detecting early carious lesions since the lesions are too shallow and do not provide enough contrast.…”
Section: Introductionmentioning
confidence: 99%